Identification of transmembrane protein 168 mutation in familial Brugada syndrome. Issue 5 (16th March 2020) - Shimizu, Akio; Zankov, Dimitar P.; Sato, Akira; Komeno, Masahiro; Toyoda, Futoshi; Yamazaki, Satoru; Makita, Toshinori; Noda, Taichi; Ikawa, Masahito; Asano, Yoshihiro; Miyashita, Yohei; Takashima, Seiji; et al.
Abstract: Brugada syndrome (BrS) is an inherited channelopathy responsible for almost 20% of sudden cardiac deaths in patients with nonstructural cardiac diseases. Approximately 70% of BrS patients, the causative gene mutation(s) remains unknown. In this study, we used whole exome sequencing to investigate candidate mutations in a family clinically diagnosed with BrS. A heterozygous 1616G>A substitution (R539Q mutation) was identified in the transmembrane protein 168 ( TMEM168 ) gene of symptomatic individuals. Similar to endogenous TMEM168, both TMEM168 wild‐type (WT) and mutant proteins that were ectopically induced in HL‐1 cells showed nuclear membrane localization. A significant decrease in Na + current and Nav 1.5 protein expression was observed in HL‐1 cardiomyocytes expressing mutant TMEM168. Ventricular tachyarrhythmias and conduction disorders were induced in the heterozygous Tmem168 1616G>A knock‐in mice by pharmacological stimulation, but not in WT mice. Na + current was reduced in ventricular cardiomyocytes isolated from the Tmem168 knock‐in heart, and Nav 1.5 expression was also impaired. This impairment was dependent on increased Nedd4‐2 binding to Nav 1.5 and subsequent ubiquitination. Collectively, our results show an association between the TMEM168 1616G>A mutation and arrhythmogenesis in a family with BrS.